Rechallenge with EGFR-TKI after failure of immunotherapy is considered an effective treatment for advanced lung adenocarcinoma patients with EGFR exon 19 deletion: a case report - Chen, Shubin; Yu, Qitao; Jiang, Wei; Lu, Yukun; Zhao, Yun; Wang, Huilin (Frontiers in Medicine, 2023)
In advanced lung adenocarcinoma patients with epidermal growth factor receptor (EGFR) mutation, epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) have an excellent and long-lasting therapeutic response; however, virtually all patients eventually develop drug resistance and experience disease progression. The use of immunotherapy after EGFR-TKIs may be a successful therapeutic option for individuals who are resistant to them. It is still unclear if EGFR-TKIs can be administered again after immunotherapy has failed. We describe a case of a 37-year-old woman who was found to have T4N3M1a stage IVa lung adenocarcinoma. Amplification refractory mutation system PCR (ARMS-PCR) genetic testing suggested EGFR exon 19 deletion. The patient was initially treated with a regimen of icotinib (125 mg tid) combined with anlotinib (8 mg qd d1-d14) with an optimal efficacy rating of partial response (PR) and was granted a PFS of 7 months. In second-line treatment, the patient received three cycles of a KN046 (KN046 is a bispecific antibody inhibitor of PD-L1 and CTLA-4) 295 mg d1, pemetrexed 800 mg d1, plus carboplatin 750 mg d1 regimen, with an optimal efficacy rating of stable disease (SD) on CT. The third-line therapy was chosen to be afatinib with docetaxel, and the patient was evaluated for PR on CT. Up to 15 August 2022, the patient had a progression free survival (PFS) of 14 months. The successful treatment of this patient is a reminder that EGFR-TKI rechallenge in EGFR exon 19 deletion patients with EGFR-TKI resistance, in which immunotherapy has failed, may be effective.